Validated analytical study of the effect of Lycopene on the pharmacokinetics of Paracetamol and Chlorzoxazone in rats - Reem Baha-Aldeen Youssef; Marwa Ahmed Fouad*; Asmaa Ahmed El-Zaher
Lycopene was reported to influence some cytochrome P450 enzymes activity. The present study investigates the effect of lycopene on the pharmacokinetics of paracetamol and chlorzoxazone. Lycopene (20 mg/kg) was intra-peritoneally administered to two groups of rats for eight consecutive days and two other groups were given vehicle. On the eighth day, chlorzoxazone and paracetamol were separately intravenously administered to a lycopene group and a control group. Blood samples were collected at different time intervals, treated and analyzed using HPLC. The HPLC method used for paracetamol analysis was based on isocratic elution using a mobile phase consisting of water: methanol, (77:23 v/v) at a flow rate 1 mL min−1, Kromasil C18 column, and UV detection at 254 nm using caffeine as internal standard. About chlorzoxazone, separation was carried out using water: acetonitrile (60: 40, v/v) as the mobile phase at a flow rate 1 mL min−1, Inertsil ODS-3 C18 column, UV detection at 283 nm and esomeprazole as internal standard. Statistical analysis of the pharmacokinetic data using student t test showed a significant increase in AUC 0-t , AUC 0-Inf and t1/2 of paracetamol (P<0.05) and of chlorzoxazone (P<0.05) in the groups pretreated with lycopene (20 mg/kg), significant increase in the volume of distribution of paracetamol (P < 0.05), but no significant difference in that of chlorzoxazone. In other words, paracetamol and chlorzoxazone showed significant decrease (P < 0.05), respectively. These results demonstrate that treatment of rats with Lycopene (20mg/kg, ip) has a significant effect on the metabolic clearance and the pharmacokinetics of both drugs.